“You will not mourn your children”: spirituality and child health in Ibadan Urban Markets. (2020)
The urban Ibadan market is not only important for its economic value, but also for its representation of the worldview of the Yoruba people of South-Western Nigeria. Yoruba urban markets are adorned with different spiritualists who also earn their livelihood in the market space. Hence, through the employment of observations and in-depth interviews, the study examines how spirituality shapes child health and mothers’ health seeking behaviours in Ibadan urban markets.